Pediatric health: mechanistic insights into inflammatory diseases and emerging therapeutic pathway-targeted approaches - Zhou, Qi; Lai, Ciai; Zhang, Minyu; Li, Rongzhen; Li, Kangjian; He, Wei (Translational Pediatrics; Vol 15, No 5 (May 31, 2026): Translational Pediatrics, 2026)
Pediatric inflammatory diseases, including juvenile idiopathic arthritis, pediatric inflammatory bowel disease, asthma, Kawasaki disease, and multisystem inflammatory syndrome in children, are an increasing global health concern. These conditions arise from dysregulated immune responses shaped by genetic susceptibility, environmental exposures, and the distinctive features of the developing pediatric immune system. This review presents a mechanism-centered overview of pediatric inflammation, emphasizing immune ontogeny, innate and adaptive immune dysregulation, cytokine signaling, inflammasome activation, oxidative stress, and the gut-immune axis. It also highlights emerging pathway-targeted therapies, including cytokine blockade, JAK inhibitors, microbiome-based interventions, and gene-editing strategies, with attention to their relevance for pediatric precision medicine. Early, mechanism-based intervention during critical developmental windows may improve long-term outcomes and reduce the lifetime burden of inflammatory disease. Overall, this review provides a concise, pediatric-focused perspective on how developmental immunology and targeted therapeutics can inform more precise and effective management of childhood inflammatory disorders.